Influence of socio-economic and behavioral risk factors on malaria prevalence: A study from Adilabad District of Telangana State. - Anjaneyulu, M.; Das, V. Vanitha (International Journal of Scientific Research in Biological Sciences, 2019)
The major burden of vector-borne disease in India comes from malaria. The biggest burden of malaria in India is often observed in backward or poor and remote parts of the country which might be due to the limited access to medical treatment or lack of knowledge on mode of malaria transmission and its preventive measures. A better understanding of the socio-economic, behavioral risk factors and knowledge gaps related to malaria infection are essential when developing coherent and effective policies Socio economic information was collected from 4872 participants in three PHCs (Jainoor, Sirpur, Lingapur) irrespective of their age and gender. The occurrence of malaria was significantly higher in individuals those don’t have schooling/primary education compared to secondary/higher education level participants. Malaria infection was observed to be elevated in households with farmers head as compared to households with daily labour or employs. The present study demonstrates that those variables related to education and poor health infrastructure are the most important factors in reducing the risk of malaria infection.